Automatic device for testing thermal resistance with thermoelectric effect - Vasiljev I. M.; Soldatov A. I. Aleksey Ivanovich; Dementjev A. A.; Soldatov A. A. Andrey Alekseevich; Abouellail A. Akhmed (2020, 2020)
Title screen